2015
DOI: 10.1039/c5ob00707k
|View full text |Cite
|
Sign up to set email alerts
|

5′-Methylene-triazole-substituted-aminoribosyl uridines as MraY inhibitors: synthesis, biological evaluation and molecular modeling

Abstract: The straightforward synthesis of 5'-methylene-[1,4]-triazole-substituted aminoribosyl uridines is described. Two families of compounds were synthesized from a unique epoxide which was regioselectively opened by acetylide ions (for compounds II) or azide ions (for compounds III). Sequential diastereoselective glycosylation with a ribosyl fluoride derivative, Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) with various complementary azide and alkyne partners afforded the targeted compounds after final deprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Recently, crystal structure of Aquifex aeolicus MraY has been published [ 34 ], and the residues (Asp 117 , Asp 118 , Asp 265 , and His 324 ) important for the activity of MraY in the active site have been elucidated [ 34 ]. The structural information of MraY from A. aeolicus sets foundations for homologous modeling of MraY from M. tuberculosis [ 34 , 35 ], which will facilitate the study on structure activity relationship (SAR) of novel chemically diverse UPA derivatives obtained by further rationale genetic engineering manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, crystal structure of Aquifex aeolicus MraY has been published [ 34 ], and the residues (Asp 117 , Asp 118 , Asp 265 , and His 324 ) important for the activity of MraY in the active site have been elucidated [ 34 ]. The structural information of MraY from A. aeolicus sets foundations for homologous modeling of MraY from M. tuberculosis [ 34 , 35 ], which will facilitate the study on structure activity relationship (SAR) of novel chemically diverse UPA derivatives obtained by further rationale genetic engineering manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…The 14 molecules investigated in this study exhibited IC 50 values typically between 50 and 100 µM. Follow-up investigation using docking models showed that the activity of the most potent inhibitors correlates with their interaction with Leu191 in TM3 of AaMraY [ 73 ]. It was suggested that the introduction of a long lipid chain on the triazole substituent drastically improved the inhibitory activity.…”
Section: Mraymentioning
confidence: 99%
“…Fer et al have also synthesised a series of triazole-containing analogues of the caprazamycins, which show IC50 values of 100-1000 µM against B. subtilis MraY, and show antibacterial activity against Staphylococcus aureus [31]. total synthesis of pacidamycin D [32], and have used the synthetic route to investigate structure-activity relationships in he N-terminal dipeptide chain [33], shown previously to be important for biological activity in the mureidomycin series [34].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%